The illusory beliefs inventory: A new measure of magical thinking and its relationship with obsessive compulsive disorder - Kingdon, Bianca; Egan, Sarah; Rees, Clare (Cambridge University Press, 2011)
Background: Magical thinking has been proposed to have an aetiological role in obsessive compulsive disorder (OCD). Aims: To address the limitations of existing measures of magical thinking we developed and validated a new 24-item measure of magical thinking, the Illusory Beliefs Inventory (IBI). Method: The validation sample comprised a total of 1194 individuals across two samples recruited via an Internet based survey. Results: Factor analysis identified three subscales representing domains relevant to the construct of magical thinking: Magical Beliefs, Spirituality, and Internal State and Thought Action Fusion. The scale had excellent internal consistency and evidence of convergent and discriminant validity. Evidence of criterion-related concurrent validity confirmed that magical thinking is a cognitive domain associated with OCD and is largely relevant to neutralizing, obsessing and hoarding symptoms. Conclusions: It is important for future studies to extend the evidence of the psychometric properties of the IBI in new populations and to conduct longitudinal studies to examine the aetiological role of magical thinking.